FOOD SECURITY OR THE RECONFIGURATION OF INDIGENOUS LIVING SPACE? A MULTI-LEVEL PERSPECTIVE ON THE FOOD ESTATE PROJECT IN SOUTH PAPUA - Andis Destrian Irianto; Rizky Fadilah; Vlaradhia Sakura Annisa Gricylla (RADJA PUBLIKA, 2026)
This study examines the Food Estate project in South Papua, Indonesia, as a contested development intervention in Indigenous territories through the Multi-Level Perspective (MLP) framework. Although officially promoted as a response to global food insecurity and national self-sufficiency, the project has generated persistent social, ecological, and political conflicts with Indigenous communities. Using a qualitative case study approach based on document analysis and secondary literature, the research analyzes interactions across landscape, regime, and niche levels. The findings show that global food crisis narratives and climate uncertainty legitimize large-scale state intervention, while centralized, corporate-driven governance marginalizes Indigenous food systems rooted in sago forests, wetlands, and agroforestry. Rather than enabling a sustainable transition, these interactions intensify structural conflict, environmental degradation, and the erosion of Indigenous food sovereignty. The study concludes that the Food Estate represents a reorganization of Indigenous living space and calls for more plural, justice-based, and ecologically embedded food governance.